THE IMPACT OF IMPAIRMENT OF ASSET VALUES ON THE FINANCIAL PERFORMANCE OF COMPANIES LISTED ON THE IRAQ STOCK EXCHANGE - Forat Sattar Hassoon Hassoon; Soulef Smaoui (Scholar Express Journals, 2024)
This study emphasizes the importance of using fair value for assets rather than book value because it more accurately reflects the asset's value in the event of a sale between parties in a regular market. Fair value is calculated on a specific date using available information and market conditions. The study investigates how asset value declines affect the financial performance of Iraq Stock Exchange-listed companies, specifically profitability and liquidity indicators, and how this information can be used to make investment decisions. It also investigates accounting procedures for asset value reductions in Iraqi businesses, proposing solutions to mitigate the effects of asset depreciation. The study, which ran from 2018 to 2022 on Iraqi industrial companies, discovered that asset value declines occur when market or fair value falls below book value. Recognizing impairment losses lowers profits, which affects dividends and limits distributions to shareholders and lenders. Companies address these declines by taking into account market value drops, negative environmental and legal changes, asset performance shifts, rising costs, and projected future losses.
Keywords: Impairment of assets; accounting standards; financial performance evaluation